Development, Implementation, and Evaluation of Treatment Guidelines for Herpes Simplex Keratitis in Sydney, Australia. Issue 7 (July 2020) - Cabrera-Aguas, Maria; Kerdraon, Yves; Symes, Richard J.; McCluskey, Peter; Samarawickrama, Chameen; Rawlinson, William; Watson, Stephanie L.
Abstract : Purpose: To develop and measure the uptake of a local guideline for herpes simplex keratitis (HSK) and to standardize initial antiviral therapy in Australia. Methods: The Registered Nurses' Association of Ontario Toolkit: "Implementation of Best Practice Guidelines" was used to develop, implement, and evaluate the guideline at Sydney Eye Hospital. An implementation team was established to reach consensus on antiviral therapy guidelines through review of available evidence, identifying stakeholders, facilitators and barriers, creating strategies for implementation, and developing a sustainability plan. An audit of all adult HSK cases during a 6-month postguideline implementation period was conducted, and the results were compared with a preimplementation audit. A web-based survey was created to assess clinician awareness, usage, and level of knowledge of the guideline. Results: Clinicians, pharmacists, and administrative staff were identified as stakeholders. Changing clinician's behavior was the major barrier to implementation. Implementation strategies included printed and online materials and lectures to clinicians. A postimplementation audit included 85 patients, and 95 clinicians received a web-based survey. The dose of the prescribed antiviral medication was in alignment with the local guideline in 80% (51/64) of the patients compared with 73% (163/223) before implementation ( P = 0.331). Stromal HSK with ulceration and keratouveitis were excluded because there were no recommendations before implementation. Over 70% of clinicians (30/41) were aware of the guideline and accessed them through educational resources. Conclusions: Guidelines for the management of HSK may improve standardization of initial antiviral therapy in HSK. In practice, most clinicians were aware of and adhered to the local guideline. Abstract : Supplemental Digital Content is Available in the Text.